PENGARUH MOTIVASI KERJA DAN KOMUNIKASI ORGANISASI TERHADAP DISIPLIN KERJA KARYAWAN (BACK OFFICE) PADA PT. SUKA FAJAR PEKANBARU - ", Novia; ", Suryalena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research supposed to know the influence of work motivation and organization communication on employee work discipline (back office) at PT. Suka Fajar Pekanbaru. Employee work discipline is one of the factors that makes the company's goals run in accordance with applicable regulations and norms. To improve work discipline, it must be investigated first what factors influence the work discipline. Discipline of employees to their work can not be separated from the motivation of the leadership, colleagues and fulfillment of employee needs in order to motivate also must be considered so that work discipline can increase. In addition to these factors, employee work discipline is strongly influenced by the ability to communicate between each element, because discipline is closely related to the delivery of existing regulations and sanctions and is accompanied by a process of coaching and supervision.The object in this research is the employee (back office) of PT. Suka Fajar Pekanbaru with a sample of 55 people calculated using the Slovin formula. Data collection methods in the research are primary data and secondary data using questionnaires, interviews and documents in the company. Analysis of the data used is to use the help of the application SPSS ver 25 for windows.This research concluded that the results of the t test showed that work motivation on employee work discipline had a significant effect on employee work discipline (back office) at PT. Suka Fajar Pekanbaru. T test results indicate that organization communication on employee work discipline there is a significant influence on employee work discipline (back office) at PT. Suka Fajar Pekanbaru. The f test results show that work motivation and organization communication simultaneously have a significant effect on accepted work discipline. Keywords: work motivation, organization communication, work discipline